Qualitative Research: The “good,” the “bad,” the “ugly” - Finlay, Linda (European Journal for Qualitative Research in Psychotherapy, 2024)
This article explores what constitutes “Good,” “Bad,” and “Ugly” qualitative research towards more fully appreciating of the nature and vision of its project. In the first two sections, I define qualitative research and map variants. Then, after highlighting qualitative evaluation criteria, I explore key issues and themes of what seems to make research “Good,” “Bad,” or “Ugly”. In the latter half of the paper, I focus specifically on four broad types of qualitative research (literature review, phenomenology, narrative-ethnographic research and discourse analysis), critically discussing a good exemplar of each. To make my strategic selections more transparent and show my role in the construction of this paper, reflexive passages are offered. Here, I engage versions of personal/introspective and methodological/contextual reflexivity plus utilise some embodied and ethical reflexivity.